A Unique Surgical Case of Ancient Calcified Intravascular Papillary Endothelial Hyperplasia in the Tibia with Knee Joint Osteoarthritis - Hironori Kitajima; Akihiro Shioya; Rie Kadoguchi; Jia Han; Hinako Sawano; Katsutaka Yonezawa; Yoshiaki Shimizu; Kentaro Hiromura; Mitsuteru Yokoyama; Takayuki Nojima; Sohsuke Yamada (Orthopaedic Surgery, 2022)
Background Intravascular papillary endothelial hyperplasia (IPEH) is a reactive lesion histopathologically characterized by papillary growth of vascular endothelial cells. IPEH is most commonly found in the skin and subcutaneous tissues of the head, neck, and extremities. Furthermore, it has been reported to occur in oral surgery, but its occurrence in bone is extremely rare. Case Presentation We present the case of a 77‐year‐old man with a chief complaint of left knee arthralgia. The knee joint X‐ray showed Kellgren–Lawrence grade 4 osteoarthritis and a mass lesion with decreased permeability within the bone in the medial part of the proximal tibia. Computerized tomography (CT) scan of the left knee showed a localized mass in the left proximal tibia with clear margins and granular internal calcification. The preoperative diagnosis was left knee osteoarthritis and a benign tumor of the left proximal tibia (enchondroma or hemangioma). The patient requested surgical treatment, so left total knee arthroplasty (TKA) and resection of the tumor were performed. The pathology revealed a rare intraosseous IPEH with marked calcification. Conclusions Since intraosseous IPEH could not be considered from the clinical findings, the pathological diagnosis was the decisive factor. This report showed the world's first case of intraosseous IPEH with marked calcification. Similar to the calcification of intraosseous hemangiomas, we considered the possibility that, in IPEH, the thrombus may fibrosis and organize in concentric circles, causing necrosis at the center and resulting in calcification. TKA was performed on the degenerative knee joint with IPEH, and a good patient outcome was obtained.